CLOTHING STYLE: MUSLIM FASHION TRENDS IN THE MODERN ERA - Ilhammuddin Arrasyid Matondang; Ikhwan Ikhwan; Zulfan Zulfan (Program Pascasarjana UIN Sumatera Utara, 2026)
This study discusses the dress code: Muslim fashion trends in modern times. The purpose of the author's research on Muslim fashion trends in modern times is to provide practical information on how to dress properly in modern times as a Muslim woman based on the Qur'an and Hadith and to add to the scientific treasury in the field of good dress codes in modern times. The type of research the author uses in this study can be said to be normative research or in other words library research. The approach and type of normative research that the author means is that the object of study being studied includes basic rules or norms of Sharia law. The author's approach is normative, namely the author tries to answer and explain what is available from applicable legal standards, then analyzes based on the theory used in referring to the Qur'an and Hadith. The results of the author's research on Muslim fashion trends in modern times are that it is not permissible to wear clothes that form the curves of the body so that women's genitals are visible, even to the point that their skin color is visible. The author quotes Sheikh al-Albani as saying,